Philothea: A Grecian Romance - Child, Lydia Maria, 1802-1880 (Salt Lake City, UT : Project Gutenberg, 2006)
"Philothea: A Grecian Romance" by Lydia Maria Child is a novel likely written during the early 19th century. The story unfolds in ancient Greece, centering around the life and perspectives of Philothea, the granddaughter of a philosopher. The narrative explores the dynamics of love, societal norms, and the intersection of personal desire with the prevailing customs and laws of Athens. The opening portion introduces readers to Athens' enchanting atmosphere under the moonlight, with vivid descriptions of its majestic architecture and the philosophical musings of its characters. Philothea, characterized by her beauty and innocence, engages in profound discussions with her friend Eudora about the presence of the gods and the fate of their loved ones. Their thoughts are clouded by their relationships, particularly regarding Philothea s deep feelings for Paralus, a nobleman who cannot marry her due to societal constraints. Tension also arises from the court's recent decision affecting Philæmon, a friend of Philothea and Eudora, casting a shadow over their lives. This intimate glimpse into their thoughts and emotions sets the stage for an exploration of love's challenges amidst the backdrop of ancient Greek culture. (This is an automatically generated summary.)
Release date is 2006-02-01
Produced by the Online Distributed Proofreading Team.
Keywords: Greece -- Fiction